2022
DOI: 10.1001/jamapsychiatry.2022.2196
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Brain Structure and Alcohol Use Behaviors in Adults

Abstract: Key Points Question Are there directional associations between cortical or subcortical macrostructure and alcohol use? Findings This mendelian randomization study including 763 874 participants in UK Biobank, Enhancing NeuroImaging Genetics through Meta Analysis (ENIGMA), Psychiatric Genomics Consortium (PGC), and GWAS & Sequencing Consortium of Alcohol and Nicotine use (GSCAN) studies identified a significant negative association between genetically predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…This analysis found evidence for a causal effect of brain structure on problematic alcohol use, including greater volume of the pars opercularis, greater thickness of the cuneus and lower volume of the basal forebrain, but no evidence for a causal effect of alcohol use on the brain when phenotypes were reversed. Consistent with these findings, a recent study using MR found evidence for a negative effect of global cortical thickness on DPW and binge drinking, with no evidence for regional effects or effect of alcohol use on the brain 72 …”
Section: Alcohol Involvement and Brain Structure: Assessing The Plaus...mentioning
confidence: 68%
“…This analysis found evidence for a causal effect of brain structure on problematic alcohol use, including greater volume of the pars opercularis, greater thickness of the cuneus and lower volume of the basal forebrain, but no evidence for a causal effect of alcohol use on the brain when phenotypes were reversed. Consistent with these findings, a recent study using MR found evidence for a negative effect of global cortical thickness on DPW and binge drinking, with no evidence for regional effects or effect of alcohol use on the brain 72 …”
Section: Alcohol Involvement and Brain Structure: Assessing The Plaus...mentioning
confidence: 68%
“…Other recent neuropsychiatric research has demonstrated that global cortical thinning, a common finding in patients who have had strokes, is associated with an increased risk for alcohol use disorder ( 1 ). As was noted on his most recent CT scan ( Figure 1 ), his brain demonstrates diffuse volume loss as well as a large region of chronic encephalomalacia.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation into the predominant neuropsychiatric mechanism is crucial to guide the overarching therapeutic approach. Plausible mechanisms to explain the change in behavior after his stroke include maladaptive coping mechanisms in the setting of new psychosocial stressors (2,3), cerebrovascular tissue injury leading to impaired neurological functioning (1,(6)(7)(8), and decompensation of a previously well-masked psychiatric illness in the setting of his stroke (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of complexity in specimen collection and prohibitive cost of TWA, gene expression analyses in response to alcohol use/misuse in living humans are often conducted with selective genes based on research hypotheses 11,12 . Apart from the published animal or in vitro studies [13][14][15] , a recent study by Marvomatis et al utilized genetic data from a large population-based GWAS to impute transcriptomic associations with alcohol consumption patterns, leveraging cis-acting genetic variants 16 . A large-scale study such as this has the advantage of mitigating some of the variability in gene expression amongst individuals.…”
Section: Introductionmentioning
confidence: 99%